Tatalaksana Awal Pasien Gagal Jantung Akut Akibat Penyakit Jantung Koroner di Ruang Emergency Pelayanan Jantung Terpadu Rumah Sakit Umum Pusat Sanglah - Cahya Ningrum, Ni Komang Sri Adelia; Suastika, Luh Oliva Saraswati; Swi Antara, I Made Putra; Wita, I Wayan (E-Jurnal Medika Udayana; Vol 12 No 8 (2023): E-Jurnal Medika Udayana, 2023)
ABSTRACT                Acute heart failure is a clinical syndrome with a complex of symptoms that is typical shortness of breath at rest or during activity. Acute heart failure is mostly caused by coronary heart disease. Coronary heart disease is a heart failure disease with narrowed coronary arteries can be caused by the buildup of a layer of fat on the walls of the coronary arteries. The purpose of this study was to determine the initial management of patients with acute heart failure due to coronary heart disease in the Integrated Heart Service Emergency Room, Sanglah Hospital. This study is a descriptive study using a cross sectional research method on a sample of 43 people who came to the PJT Emergency Room at Sanglah Hospital with a diagnosis of acute heart failure due to coronary heart disease in 2019-2020. The data that has been obtained were then analyzed using SPSS version 24. The results showed that most of the patients 30 sample (69.77%) were male compared to women, there were 13 sample (30.23%). The majority of patients with acute heart failure due to coronary heart disease come to the Emergency Room with complaints of shortness of breath. Initial treatment given in the Emergency Room included intravenous diuretic Furosemide with a dose range of 20-80 mg/IV (93.02%), Beta blockers (2.35%), Nitroglycerin (13.95%), Digoxin (13.95%), and Dobutamine (30.23%). Most of the patients in this study were given Furosemide as an initial treatment according to the PERKI 2020 guidelines which suggest the administration of Furosemide as a treatment for fluid congestion in acute heart failure. Some patients require inotropic support such as Dobutamine which is adjusted according to individual clinical criteria. Supporting examinations were carried out on all study samples (100%) including electrocardiogram (ECG) and chest X-ray examinations. Keywords: Acute heart failure, Coronary heart disease, Initial management